Pengaruh Citra Merek, Gaya Hidup, dan Harga terhadap Keputusan Pembelian Smartphone Oppo: Survei Pada Pengguna Smartphone Merek Oppo di Sragen - Siti Khusnul Hotimah; Kusna Djati Purnama (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The purpose of this study was to analyze and test influence of brand image, lifestyle and price on purchasing decisions for Oppo brand smartphone in Sragen. The type of data usedpopulation in this study is an unknown number of Oppo brand smartphone consumers in Sragen. The sampling technique in this study used a non-probability sampling technique with a purposive sampling method of 100 respondents. The data analysis techniques used are validity, reliability, classical assumption test, descriptive analysis, multiple linier regression analysis, t test, F test and coefficient of determination test. The results of this research obtained Y = 2,178 + + 0,323 X1 + 0,283 X2 + 0,185 X3. The results t test results show that brand image, lifestyle, and pricehave asignificant influrnce on purchasing for Oppo brand smartphones. The F test results obtained indicate that the regression results used are correct. The coefficient of determination test result is 0,774, meaning that the contribution of brand image, lifestyle and price to purchasing decisions is 77,4%, so the remaining 22,6% is influenced by other factors outside the variables studied.